2015
DOI: 10.1111/jvim.13588
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Extended Release Levetiracetam in Normal Healthy Dogs After Single Oral Dosing

Abstract: BackgroundLevetiracetam is an anticonvulsant used for control of canine epilepsy. An extended release preparation should improve dosing convenience.ObjectivesTo determine the disposition of extended release levetiracetam in normal dogs after single dosing.AnimalsPharmacokinetic study: 16 healthy, adult dogs.MethodsUsing a partially randomized crossover study, levetiracetam (30 mg/kg) was administered intravenously (IV) and orally (PO) as extended release preparation with or without food. Blood was collected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…This gradual change in serum concentration is proposed to result in fewer undesirable effects as well as to decrease the risk of therapeutic failure arising from subtherapeutic concentrations . Our findings are in agreement with those of previous studies comparing IRL and XRL in dogs and humans …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This gradual change in serum concentration is proposed to result in fewer undesirable effects as well as to decrease the risk of therapeutic failure arising from subtherapeutic concentrations . Our findings are in agreement with those of previous studies comparing IRL and XRL in dogs and humans …”
Section: Discussionsupporting
confidence: 92%
“…At the time of sample analysis, serum samples were thawed at room temperature and then vortexed to assure homogeneity. Levetiracetam was detected and quantitated in feline serum by a Food and Drug Administration‐approved immunoassay for use in humans on a general chemistry analyzer, which is described elsewhere . The assay had been previously validated in cats .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetics of levetiracetam have been extensively evaluated in human patients, dogs, cats, and, more recently, in adult horses [13,14,[22][23][24][25][26]. The results of the current study in foals are similar to those reported in adult horses [14] with minor differences in elimination half-life, volume of distribution and clearance that are likely attributable to agerelated differences in these mechanisms.…”
Section: Discussionsupporting
confidence: 69%
“…The package insert for the assay indicates a lack of cross‐reactivity with the major metabolite (L057/PBA) (ARK website). The accuracy and precision of the assay for quantitation of levetiracetam in serum was confirmed by comparing known amounts of LEV added to equine serum when measured by the immunoassay, as previously performed in dogs (Beasley & Boothe, ). LEV was detected in equine serum, to which the upper limit of quantitation was 150 μg/ml, and the lower limit of quantitation was 2 μg/ml.…”
Section: Methodsmentioning
confidence: 99%